Perancangan Steganografi Penyisipan Pesan Teks pada Citra Digital Menggunakan Pixel Value Differencing - Saputra, David; Witanti, Arita (JMAI (Jurnal Multimedia & Artificial Intelligence), 2020)
Message security in this modern is needed. The development of the internet network that allows people to exchange data through the internet network. Along with the development of the internet, communication and information technology crimes are also developing one of which is data theft. These problems can be dealt with using the sciences that have existed since time immemorial namely steganography. Steganography is a technique that can secure the message by hiding the message pasted through the media in the form of digital images. Pixel Value Differencing as one of steganography techniques is quite safe in hiding secret messages. Pixel Value Differencing is a steganographic method that uses a difference value between two pixels to determine how many secret bits can be inserted. Based on the test results, it can be concluded that by using the pixel value differencing (PVD) method, the capacity of the image to insert a message is smaller than the image size, the processing time in this method is quite fast, the image quality after inserting a message has good quality